Survival of Conidia of Discula destructiva in Frass of the Convergent Lady Beetle - Hed, Bryan E (Plant disease, 1999)
The survival of conidia of Discula destructiva in frass of convergent lady beetles (Hippodamia convergens) was investigated. D. destructiva was isolated from frass pellets of 76% of adult convergent lady beetles exposed to D. destructiva for 1 h. Of the beetles from which D. destructiva was initially isolated, more than 80, 32, 19, 13, and 12.5% retained viable conidia of D. destructiva internally for at least 12, 24, 48, 72, and 96 h, respectively. Numbers of conidia, estimated with a hemacytometer, ranged from 0 to 3.2 × 106 conidia per frass pellet